Al-qiyam at tarbawiyyah fi sûrati maryam al âyah 16-21 fi tafsîri “fi dzilâli al-qur’ân li sayyid qutb - Agus Budiman; Rumbiati Rumbiati (At-Ta'dib, 2018)
The Quran is the source of education that contains the doctrine, worship, wisdom, literature, stories, advice, guidance and so on. Sayyed Qutb in his interpretation in the shadows of the Qur’an, "Turns out about attending the Quran activity and the situation pleased as the first descent to the Messenger of God, to be inspired works as used to the past work and facilitates the understanding and studies on educational values which relate to human life with the doctrine and ethics”. In this research, the researcher used the descriptive analytic method to illustrate and discuss existing issues in order to understand the content of these issues and the knowledge of the research method in the Content Analytical Method to visualize the relevant. The result reached by the investigators on educational values in Surat Maryam Ayat 16-21 in an interpretation in the shadow of the Quran to Sayyid Qutb includes: (1) Monotheistic values are the call that contains the way to unite the people of the faith, (2) Moral values, which are an example of moral ethics and an invitation to preserve the dignity of women as well as the value of trusting God in all cases. The researcher suggests readers to: (1) Understand the interpretation of the Koran more detailed and good. (2) Knowing the values of education as contained in Surat Maryam verse 16-21. A specific references and value in-depth coverage of the researcher values moral doctrine.